Pengembangan Ketrampilan Pengolahan Susu Sapi Pada Komunitas Fatayat NU Krajan Bedrug Pulung Ponorogo - Nurhadi Sasmito; Teguh Ansori (Social Science Academic, 2025)
In Dukuh Krajan, Bedrug Village, Pulung District, Ponorogo Regency, there is potential for the majority of residents whose work is as dairy farmers, namely cow's milk. Cow's milk is sold raw to cow's milk collectors, while the selling price follows the price of collectors who are erratic or unstable. When the price of cow's milk fell, some residents already processed it themselves, but due to a lack of knowledge on how to process it, they just boiled it so it smelled fishy and many didn't like drinking it. This community service aims to raise the skill potential of Fatayat NU members with skills development training through processing raw cow's milk into ready-to-consume milk. This service uses the Asset Based Community Development (ABCD) method. The results of this training are the skills of Fatayat NU members in processing raw cow's milk into delicious ready-to-consume milk, interest in being consumed by children, the community and being able to develop the economy of Fatayat NU members Dukuh Krajan, Bedrug Village, Pulung District, Ponorogo Regency.